Open-Play Dominance and Set-Play Efficiency in Men’s Indoor Hockey: Goal-Scoring Patterns at the 2025 SEA Games - Ilham Wiranata Kusuma; Achmad Widodo; Himawan Wismanadi; Taufiq Hidayat; Pudjijuniarto Pudjijuniarto; Heryanto Nur Muhammad (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2027)
The purpose of the study. This study aimed to investigate and characterize the goal-scoring patterns exhibited in the men’s indoor hockey tournament at the 33rd Southeast Asian Games (SEA Games) 2025, held in Bangkok, Thailand. Specifically, the research sought to identify the predominant methods of goal creation, temporal distributions of goals within match periods, spatial zones of shot origin, and the relative contribution of set-piece situations to overall scoring outcomes. Materials and methods. A retrospective observational design employing systematic notational analysis was adopted. All thirteen matches of the men’s indoor hockey tournament were analyzed using official broadcast footage. A validated coding instrument was applied to classify each goal (N = 120) according to type of attack (open play, penalty corner, set piece), field zone of origin, temporal segment within each half, and player involvement. Descriptive statistics, chi-square tests of independence, and frequency analyses were computed to examine distributional patterns and associations among variables. Inter-rater reliability was assessed using Cohen’s kappa (κ ≥ 0.85). Results. Open-play attacks constituted the primary source of goals (58.3%), followed by penalty corners (26.7%) and other set pieces (15.0%). A statistically significant temporal clustering of goals was observed in the final ten minutes of each half (χ² = 14.82, p < .01), with 41.7% of all goals scored in these segments. Goals originating from the central corridor of the shooting circle were significantly more prevalent than those from lateral positions (p < .05). Teams that scored the first goal won 76.9% of their matches, and a significant positive association was found between the ratio of penalty corner conversion and final match outcome (χ² = 9.67, p < .01). Indonesia, the eventual gold medalist, exhibited the highest shooting efficiency and the most diversified attacking repertoire. Conclusions. Goal-scoring in men’s indoor hockey at the SEA Games 2025 was predominantly driven by open-play transitions and penalty corner efficiency. The temporal concentration of goals in late-half segments underscores the tactical importance of fitness-related endurance and strategic substitution management. These findings offer evidence-based insights for coaching staff, performance analysts, and national federations seeking to optimize tactical preparation for major regional and international indoor hockey competitions.